The Emotional Experience of In-Service English Language Teachers During Pandemic Virtual Classrooms - Lusiana Pratiwi; Joko Nurkamto; Kristian Adi Putra (AL-ISHLAH: Jurnal Pendidikan, 2023)
The paper reports on an in-depth. A narrative inquiry of the emotional experience of in-service English teachers during virtual pandemic classrooms. The data are derived from the teachers’ semi structured-interviews. The data were analyzed with Andy Hargreaves’s emotional geography framework, which focuses on the physical aspects of schooling. Through five stories that recount their experiences in different physical emotional geography, they understand and misunderstand different aspects of schooling during virtual pandemic classrooms. The stories will raise various physical geography emotions, both positive and negative emotions. They will need them to create strategies to manage their emotions. In conclusion, as teachers, they need to understand each other’s work emotionally.